A comparison of B- and A-type nanoparticles on pressure resistance. (October 2022) - Pu, Huayin; Chen, Xuyan; Wang, Jiankang; Niu, Wei; Li, Yanjun; Zhang, Chong; Liu, Gemei; Huang, Junrong
Abstract: Characterizing the waxy maize starch nanoparticles (SNPs) with different crystal types (B- and A-type) under ultra-high pressure (UHP) treatment is important in understanding the processes underpinning starch and starchy food processing. Here, The changes of structural characteristics of SNPs with B- and A-type under UHP treatment were investigated. Compared with B-type nanoparticles, the surface morphology of the A-type nanoparticles was less affected, the gelatinization temperatures ( T o, T p, T c ) were higher, the enthalpy ( ∆H ) showed a faster reduction, the reduction rate in parameters related to the long-range ordered structure (relative crystallinity, fractal dimension) was lower. This indicated B-type SNPs were more prone to helix-helix dissociation while the double helices from A-type SNPs were inclined to unwind. In general, the pressure resistance of B- and A-type SNPs showed significant difference, which was distinguished from those for native B- and A-type starches. Highlights: The pressure resistance of A- and B-type starch nanoparticles (SNPs) was compared. Difference in pressure resistance for SNPs was distinguished from those for starches. A-type SNPs had lower reduction rate in relative crystallinity and fractal dimension. A- and B-type SNPs had more stable single helix and double helices, respectively. A- and B-type SNPs helices were prone to dissociation and unwinding, respectively.